Unformatted text preview: ) = ax n ! dF ( x ) dx = nax n & 1 F ( x ) = a ln x ! dF ( x ) dx = a x Basic manipulations & x y ± a b = ² y x ³ & a b = 1 ( y x ) a b x a x b = x a + b x a x b = x a & b x a b = y , x = y b a ln x + ln y = ln( xy ) ln x & ln y = ln( x=y ) a ln x = ln x a Roots of a quadratic equation Suppose you want to solve all x for which ax 2 + bx + c = 0 : The solution is given by & b ± p b 2 & 4 ac 2 a 1...
View
Full Document
 Spring '07
 Eastin
 Business, Utility, Probability theory, Quadratic equation, Trigraph

Click to edit the document details